2014
DOI: 10.1186/s12865-014-0029-0
|View full text |Cite
|
Sign up to set email alerts
|

Capturing needles in haystacks: a comparison of B-cell receptor sequencing methods

Abstract: BackgroundDeep-sequencing methods are rapidly developing in the field of B-cell receptor (BCR) and T-cell receptor (TCR) diversity. These promise to revolutionise our understanding of adaptive immune dynamics, identify novel antibodies, and allow monitoring of minimal residual disease. However, different methods for BCR and TCR enrichment and amplification have been proposed. Here we perform the first systematic comparison between different methods of enrichment, amplification and sequencing for generating BCR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 43 publications
0
39
0
Order By: Relevance
“…Detection of very low-level B-ALL sequences in some qPCR-negative samples was reproducible in replicates of the same sample, with the exception of one sample (Supplementary Table S4, patient 1611, day 19 sample), from which clonotypic sequences were detected at low frequency (0.0656%) in only one of two repeats in keeping with stochastic ‘loss' of a rare variant. 8, 25, 26, 27 Likewise, the percentage of matching BCR sequences in DNA samples (UKALL XI) correlated with the % blasts in PB (Figure 1b). Notably, we detected clonotypic sequences in 6 of 10 patients at day 28, where blasts were not detected (<1%).…”
Section: Resultsmentioning
confidence: 81%
See 3 more Smart Citations
“…Detection of very low-level B-ALL sequences in some qPCR-negative samples was reproducible in replicates of the same sample, with the exception of one sample (Supplementary Table S4, patient 1611, day 19 sample), from which clonotypic sequences were detected at low frequency (0.0656%) in only one of two repeats in keeping with stochastic ‘loss' of a rare variant. 8, 25, 26, 27 Likewise, the percentage of matching BCR sequences in DNA samples (UKALL XI) correlated with the % blasts in PB (Figure 1b). Notably, we detected clonotypic sequences in 6 of 10 patients at day 28, where blasts were not detected (<1%).…”
Section: Resultsmentioning
confidence: 81%
“…We have previously shown that there is a strong linear correlation in the frequencies of functional BCRs between RNA and DNA from the same sample. 27 Here, by studying three patients with both DNA and RNA available from the same B-ALL sample, we find that DNA-amplified B-ALL BCR sequences represented a much higher percentage of total BCR sequences than RNA-derived ones (Supplementary Figure S2), most likely due to differences in RNA expression between B-cell subsets and differences in RNA stability the B-ALL clone compared with their healthy B-cell counterparts. 30, 31 Therefore, the RNA BCR repertoire, although very powerful in detecting low-level MRD, appears to underestimate the absolute fraction of residual B-ALL cells in a sample.…”
Section: Resultsmentioning
confidence: 82%
See 2 more Smart Citations
“…Comprehensive assessment of the T cell repertoire entails knowing both the diversity (the number of unique clonotypes) and the relative abundance of these clonotypes (number of reads per clonotype), which can be obtained simultaneously by NGS using genomic DNA (gDNA) or mRNA templates. Although differences in TCRβ mRNA quantity per cell exist [42, 43], clonal rank derived from mRNA abundance correlates well with those quantified from sorted cell population [42, 44] or its corresponding gDNA [45]. Therefore, in this study we used mRNA extracted from blood to evaluate the T cell repertoire of HC and SLE subjects.…”
Section: Discussionmentioning
confidence: 99%